Biochemical Investigation in Blood Serum of Female Patients in Type-2 Diabetes - Alaa Abbas Fadhel (Journal of Global Pharma Technology, 2018)
Type-2 diabetes mellitus (DM) is considered as a chronic defect of glucose metabolism linked to deficiency of insulin or and resistance to the insulin action. This cross-section study includes forty-three female patients in type-2DM (50 ± 7 years old), with diabetes duration of10±4 years and thirty-six healthy subjects matched in the age and sex with patients as control. Fasting blood specimens were collected from both patients and healthy control. Serum blood level of zinc, magnesium, manganese, triglyceride (Tg), total cholesterol (Tc), alanine amino transferase (ALT), and g-glutamyl transpeptidase (GGT) were evaluated and investigated. The results indicated that there is a significant decrease in Zn, Mg, and Mn serum concentration levels in female type-2 DM compared to control group (p £ 0.05) which supports the close association of the above elements with glucose metabolism. Serum triglyceride (Tg), and total cholesterol (Tc) levels were significantly higher compared with the healthy control subjects (p £ 0.05). while the results concerning to liver enzymes showed significant elevation in the mean level of ALT and GGT enzymes in compared with healthy subjects. The achieved results might be functioned as predictors for coronary heart disease and suggest that the measurement of serum liver enzymes could be signed as a biomarker for type-2 diabetes mellitus disease.Keywords: Type-2 diabetes, Trace elements, Lipid parameters, ALT, GGT,